Neutrophil Effector Functions Are Not Impaired in Duffy Antigen Receptor for Chemokines (DARC)-Null Black South Africans - Naidoo, Kewreshini K.; Ngubane, Ayanda; Gaza, Pedzisai; Moodley, Amber; Ndung'u, Thumbi; Thobakgale, Christina F. (Frontiers in Immunology, 2019)
Neutrophils are well recognized for their pathogen killing mechanisms and disorders of neutrophil count and function are associated with recurrent infections. The Duffy Antigen Receptor for Chemokines (DARC)-null genotype is predominant in sub-Saharan African ancestry populations and is the major genetic determinant of benign ethnic neutropenia which has been associated with increased risk of Human Immunodeficiency Virus (HIV)-1 acquisition and mother-to-child transmission. However, the impact of DARC-null-linked neutropenia on HIV disease progression remains controversial. While the DARC-null genotype is associated with low numbers of circulating neutrophils, the effects of the polymorphism on neutrophil functions is unknown. We investigated the impact of the DARC-null trait and lower absolute neutrophil counts (ANCs) on key neutrophil effector functions (proteolytic activity within the phagosome following Fc receptor-mediated phagocytosis, reactive oxygen species (ROS) production and neutrophil extracellular trap (NET) formation) in 20 HIV negative and 22 HIV-1 chronically infected black South Africans. Phagosome maturation was measured by flow cytometry following Fc-mediated uptake of IgG opsonized beads; ROS production was measured by chemi-luminescence after activation of neutrophils with phorbol 12-myristate 13-acetate (PMA). Activated neutrophils were also visualized by fluorescent microscopy for NET quantification. Study subjects were genotyped for the DARC trait using TaqMan allelic discrimination assays and ANCs were measured by full blood count. As expected, the DARC-null polymorphism was highly prevalent in our participant cohort (69%) and was strongly associated with lower ANCs in uninfected (p=0.0007) and HIV-1 infected (p=0.03) subjects. We observed enhanced proteolytic activity within the phagosome in the absence of DARC at 10 minutes (p=0.05 and p=0.009) and 60 minutes (p=0.05 and p=0.07) in uninfected and HIV-1 infected subjects respectively. ROS was unaffected by DARC trait irrespective of HIV status. Furthermore, formation of NETs was reduced in neutrophils from DARC-null subjects (p=0.04) following prolonged in vitro stimulation, but only in HIV-1 infected subjects. The data indicate differential neutrophil function in the absence of DARC that may be moderately modulated by HIV-1 infection but overall, the data suggest that DARC-null trait is not deleterious to neutrophil effector functions in African populations.